ANALYSIS AND VERIFICATION OF FIRE DANGER RATING SYSTEM (FDRS) PARAMETERS IN LAND AND FOREST FIRE IN WEST KALIMANTAN IN 2019 AND ITS RELATIONSHIP WITH HOTSPOTS AND RAINFALL - Putri Amelia, Jihan
Land and forest fires in 2019 have an adverse impact on Indonesia, one of them is West Kalimantan. The government is trying to develop an early warning system called the FDRS. However, the utilization of FDRS still requires verification on the actual events of fires and a study of its relationship with hotspot distribution and rainfall. This study aims to analyze and verify FDRS parameters in the 2019 land and forest fires in West Kalimantan as well as their relationship to hotspots and rainfall. The data used in this study is FDRS’s data in 2019 (from LAPAN). Meteorological observation data, hotspot (from MODIS Terra-Aqua), and burnt area data (from KLHK) for verification. The analysis in this study was conducted using correlation method (r) and coefficient of determination (R2). The results showed that the value of the FFMC, DC, ISI, and FWI parameters over the burnt area in West Kalimantan in 2019 ranged from 48 to 89, 6 to 733, 0 to 5, 0 to 23. The FDRS parameter was strongly affected by the rainfall conditions 21 days before the fire incident (???? ? = -0.54 to -0.66) and the number of days with light rainfall before the fire incident (???? ? = 0.54 to 0.61). In the upper class of each FDRS parameter, the number of hotspots will increase (???? ? = 0.62 to 0.68) and the burnt area as well (???? ?= 0.64 to 0.74). Furthermore, about 27.85% of fire events were affected by rainfall conditions 21 days before the fire event and about 28.51% of fire events were also affected by the number of days with light rainfall (<20 mm/day) before the fire event. The findings also showed that about 70.48% of fire events could be identified based on the number of hotspots. Point out that the FDRS has a good ability to perceive land and forest fires that occurred in West Kalimantan in 2019.